LPS Cooperates with Poly-L-Arginine to Promote IL-6 and IL-8 Release via the JNK Signaling Pathway in NCI-H292 Cells - Ling-Ling Zhang; Bing Chen; Xiao-Yun Fan; Sha-Sha Wu; Sheng-Quan Zhang; Hui-Mei Wu (Journal of Immunology Research)
Objective. Herein, we aimed to study the mechanism whereby poly-L-arginine (PLA) and lipopolysaccharide (LPS) can synergistically induce the release of interleukin-6 (IL-6) and IL-8 in NCI-H292 cells. Methods. NCI-H292 cells were divided into control, PLA, LPS, and PLA+LPS groups. At various time points, the phosphorylation of JNK in each group was measured by western blotting. Additionally, the productions of IL-6 and IL-8 were assessed using an enzyme-linked immunosorbent assay (ELISA). The effects of SP600125, an inhibitor of the JNK pathway, on the increase of p-JNK, IL-6, and IL-8 were also studied. Results. Our results showed that either PLA or LPS treatment alone can significantly increase the phosphorylation level of JNK in NCI-H292 cells. Of interest was the combined use of PLA and LPS that has a synergistic effect on the phosphorylation of JNK, as well as synergistically inducing the release of IL-6 and IL-8 in NCI-H292 cells. Furthermore, SP600125 significantly inhibited the activation of JNK signal, as well as reducing the productions of IL-6 and IL-8 in response to PLA+LPS stimulation. Conclusions. The JNK signaling pathway contributes to the release of IL-6 and IL-8, which is stimulated by the synergistic actions of PLA+LPS in NCI-H292 cells.